Ionic and stable isotopic content in two Antarctic firn cores under different environment settings - ILHA, JOÃO G.; SIMÕES, JEFFERSON C.; PORTELLA, MANOELA B.P.; BERNARDO, RONALDO T.; THOEN, ISAÍAS U.; CASASSA, GINO (My University, 2023)
Abstract This article compares isotopic, ionic and climatic data from two firn cores from the West Antarctic Ice Sheet (WAIS). The IC-02 (88°01'21.3"S , 82°04'21.7"W) and the IC-05 (82°30'30.8"S , 79°28'02.7"W) closer to the coast. The IC-02 had 488 samples analyzed covering 14.58 meters depth while the IC-05 had 602 samples analyzed covering 19.73 meters depth. The time interval for both ice cores is 25 years ranging from 1978 to 2003. Sodium, sulfate and chloride were analyzed via ion chromatography using three DionexTM ionic chromatographers at the laboratories of Centro Polar e Climático (CPC) and at the Climate Change Institute. Stable isotope data was determined using cavity ring-down spectroscopy in a Picarro® spectrometer at the CPC. Annual accumulation was greater at IC-05 with an average of 0.35 m.eq.w.a-1 compared to 0.25 m.eq.w.a-1 at the IC-02. Stable isotope data was approximately 1.3 times more negative at the IC-02 which also presented higher d values. Na+ and Cl- were in higher concentrations at the IC-05 however Cl/Na was greater in the IC-02. The Cl excess was found to be derived from fractionation of sea salt aerosols and not related to volcanism. This work presents new insights regarding the chemical differences between ice cores.
Keywords: antarctica; ice core; ionic content; stable isotopes